ALVEOLAR BONE REGENERATION AFTER DEMINERALIZED FREEZE DRIED BONE ALOGRAFT (DFDBA) BONE GRAFTING - Sri Oktawati (Faculty of Dentistry, Universitas Indonesia, 2006)
Periodontal treatment by conventional way will result in healing repair, which easily cause recurrence. Modification of treatment should be done to get an effective result, that is the regeneration of alveolar bone and to reduce inflammation. The objective of this study is to determine the alveolar bone regeneration after using DFDBA (Demineralized Freeze Dried Bone Allograft). Quasi experimental designs with pre and post test method was used in this study. From 13 patients, 26 defects got conventional or regenerative treatment. The indicator of alveolar bone regenaration in bone height in radiographic appearance and level of osteocalsin in gingival crevicular fluid (GCF) were checked before and after the treatment, then the changes that occurred were analyzed. The result of the research showed that alveolar bone regeneration only occurred to the group of regenerative treatment using DFDBA. The conclusion is the effective periodontal tissue regeneration occurred at regenerative treatment by using DFDBA, and the osteocalsin in GCF can be used as indicator of bone growth.